Comprehensiveness of the Divine Scripture and Mutual Expectations of Religion and Man - Āyatullāh abdullah Jawādī Amulī (حکمت اسرا, 2011)
Having the best life in the world, requires knowledge (al-maÝrifa) as well as a world-adorning. These two requirements have numerous responses the most perfect and rational of which are the religious ones. Thus, human being seeks from religion the ways of organizing, acquiring knowledge of and adorning the world. God’s religion shows him these ways. Likewise, religion expects man not to lose his intellectual, experiential and artistic wealth by engaging in unsuccessful activities and drifting aimlessly through life.